Erectile and Sexual Function Determinants in Men with Type 1 Diabetes - Cristian Petolicchio; Francesco Cocchiara; Giordano Spacco; Eliana Delle Chiaie; Maria Grazia Calevo; Davide Carlo Maggi; Diego Ferone; Nicola Minuto; Marta Bassi (Diabetology)
Background/Objectives: The association between sexual dysfunctions and diabetes is largely known, but few studies investigated its prevalence in Type 1 Diabetes (T1D). The aim of this study was to evaluate the prevalence of sexual dysfunction in a group of men with T1D regardless of their age and to compare the prevalence in men treated with different intensive insulin regimens. Methods: The study population included 68 men affected by T1D, of whom 17 were on Multiple Daily Injections (MDI) and 51 were on Continuous Subcutaneous Insulin Infusion (41 on Advanced Hybrid Closed Loop System with catheters and 10 on patch pumps). All participants completed the International Index of Erectile Function (IIEF-15), which evaluates several domains of sexual function. Another questionnaire that evaluated general features, diabetes-specific features, and sexual-specific features was proposed to every participant. Results: The overall prevalence of erectile dysfunction was 48.5%, and the overall prevalence of a severe grade of erectile dysfunction was 26.5%. Correlations were demonstrated between the prevalence of erectile dysfunction and age and between the prevalence of erectile dysfunction and dyadic status. Age and dyadic status were also correlated with lower scores in several other domains of the IIEF-15 questionnaire. Conclusions: Men with Type 1 Diabetes present a high prevalence of erectile dysfunction, independent of glycometabolic control of the disease and insulin regimens; on the contrary, a great correlation is demonstrated with age and dyadic status.